Use of Hepatitis C Nucleic Acid Test–Positive Liver Allografts in Hepatitis C Virus Seronegative Recipients. Issue 5 (21st April 2020) - Anwar, Nadeem; Kaiser, Tiffany E.; Bari, Khurram; Schoech, Michael; Diwan, Tayyab S.; Cuffy, Madison C.; Silski, Latifa; Quillin, Ralph C.; Safdar, Kamran; Shah, Shimul A.
Abstract : Because of underutilization of liver allografts, our center previously showed that hepatitis C virus (HCV) antibody–positive/nucleic acid test (NAT)–negative livers when transplanted into HCV nonviremic recipients were safe with a 10% risk of HCV transmission. Herein, we present our single‐center prospective experience of using HCV NAT+ liver allografts transplanted into HCV NAT– recipients. An institutional review board–approved matched cohort study was conducted examining post– liver transplantation (LT) outcomes of HCV– patients who received HCV NAT+ organs (treatment group) compared with matched recipients with HCV NAT– organs (matched comparator group) between June 2018 to October 2019. The primary endpoint was success of HCV treatment and elimination of HCV infection. The secondary outcomes included the 30‐day and 1‐year graft and patient survival as well as perioperative complications. There were 32 recipients enrolled into each group. Because of 1 death in the index admission, 30/31 patients (97%) were given HCV treatment at a median starting time of 47 days (18‐140 days) after LT. A total of 19 (63%) patients achieved sustained virological response at week 12 (SVR12). Another 6 patients achieved end‐of‐treatment response, while 5 remained on therapy and 1 is yet to start treatment. No HCV treatment failure has been noted. There were no differences in 30‐day and 1‐year graft and patient survival, length of hospital stay, biliary or vascular complications, or cytomegalovirus viremia between the 2 groups. In this interim analysis of a matched cohort study, which is the first and largest study to date, the patients who received the HCV NAT+ organs had similar outcomes regarding graft function, patient survival, and post‐LT complications.